Decoding purchase decisions: The interplay of brand image, courtesy, and religiosity - Kurniawan, Heri (Journal of Management and Digital Business, 2023)
This study investigated the impact of Brand Image, Courtesy, and Religiosity on Purchase Decisions among Gen Z consumers in Central Java Province. A quantitative research approach was employed, utilizing Structural Equation Modeling (SEM) to analyze data collected from 400 respondents. The findings indicated that both Brand Image and Courtesy had significant positive effects on Purchase Decisions. Additionally, Religiosity was found to mediate these relationships significantly, highlighting its crucial role in shaping consumer behavior. These results suggest that integrating cultural and religious values into marketing strategies can enhance customer engagement and loyalty. The study provides new insights into the interplay between brand perception, interpersonal interactions, and personal values in influencing consumer decisions. This research underscores the importance of culturally and religiously sensitive marketing practices for effectively engaging and retaining customers. The implications of these findings are significant for both marketers and academics, providing a foundation for future research in consumer behavior and marketing strategy.